2015
DOI: 10.1136/annrheumdis-2014-206696
|View full text |Cite
|
Sign up to set email alerts
|

Step-down strategy of spacing TNF-blocker injections for established rheumatoid arthritis in remission: results of the multicentre non-inferiority randomised open-label controlled trial(STRASS: Spacing of TNF-blocker injections in Rheumatoid ArthritiS Study)

Abstract: ClinicalTrials.gov: NCT00780793; EudraCT identifier: 2007-004483-41.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 40 publications
7
118
1
5
Order By: Relevance
“…In a cohort of 51 RA patients with Ifx Van der Maas et al observed that dose titration was feasible in patients with inactive disease and also demonstrated important cost savings with this strategy [4]. Recently, two randomized controlled trials on tapering of Ada and Etn in RA patients executed in daily clinical practice have been published [12,14]. Both clinical trials conclude that tapering is feasible in RA patients without impacting structural damage progression [12] or the appearance of flares [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cohort of 51 RA patients with Ifx Van der Maas et al observed that dose titration was feasible in patients with inactive disease and also demonstrated important cost savings with this strategy [4]. Recently, two randomized controlled trials on tapering of Ada and Etn in RA patients executed in daily clinical practice have been published [12,14]. Both clinical trials conclude that tapering is feasible in RA patients without impacting structural damage progression [12] or the appearance of flares [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two randomized controlled trials on tapering of Ada and Etn in RA patients executed in daily clinical practice have been published [12,14]. Both clinical trials conclude that tapering is feasible in RA patients without impacting structural damage progression [12] or the appearance of flares [14]. Furthermore, published data suggest that a tapering strategy may be efficient to maintain remission or LDA in most patients with axial spondyloarthritis [9,10,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Целью открытого РКИ STRASS (Spacing of TNF-blocker injections in Rheumatoid Arthritis Study) было изучение ре-зультатов снижения дозировки ГИБП за счет прогрес-сивного увеличения интервала между инъекциями ЭТЦ (50 мг/нед) и АДА (40 мг/2 нед) по сравнению со стандар-ной схемой [22]. Такие пациенты не менее 1 года получали ингибиторы ФНОα в виде монотерапии или в комбинации с БПВП (МТ или лефлуномид), находились в ремиссии ≥6 мес и не имели за последний год прогрессирования структурных изменений.…”
Section: снижение дозировки ингибиторов фноαunclassified
“…Так, например, значения индекса DAS28 >2,2 при инициировании отмены препара-та, присутствие ревматоидного фактора и антител к цикли-ческому цитруллинированному пептиду (АЦЦП) являются факторами риска обострения заболевания [14,15,22,30]. Считается, что продолжение терапии БПВП после отмены ГИБП способствует сохранению ремиссии.…”
Section: предик торы обостренияunclassified